Mahasiswa Belajar Berinvetasi Saham, Kenapa Tidak? Pentingnya Minat Investasi Serta Literasi Keuangan Pada Mahasiswa Yang Berinvestasi Saham. - Fitriyana, Mifta (Journal Competency of Business, 2023)
Students are agents of change, because they are still young and realize that they can take advantage of their current youth to become young investors. In the world of investment, information is something that investors really need. Investors cannot be separated from information to determine their investment policies. From the investment process there is the determination of investment policy where investors need to determine what the objectives are (return and risk) and how much investment will be made to securities analysis to portfolio formation. This indicates the importance of financial literacy that investors must have. With the trend that there are students who have also started to become young investors by owning shares and investing practices, it makes students interested in investing also have an interest.